Schooling Forsaken: Education and Migration - Ilhom Abdulloev; Gil S. Epstein; Ira N. Gang (Global Labor Organization (GLO), 2020)
We examine the phenomenon of forsaken schooling resulting from opportunities abroad. The brain-drain/gain literature takes as its starting point the migration of educated/professional labor from poor origin countries to richer host countries. While high-skilled emigration is troubling, even more so is that many international migrants accept low-skilled positions in host countries. Their willingness to do so arises from very large host-home earnings differentials. At home this can lead to reduced educational investment as people forgo schooling because of opportunities to migrate to high paying low-skilled jobs. This suggests possible time-inconsistencies between short-run economic gains from migration and negative long-term effects from missing human-capital investment. We analyze data from Tajikistan, where approximately one-third of the labor force works outside of the country. Our empirical results establish circumstances under forsaken schooling occurs, leaving trade-offs that policymakers' need consider.
Keywords: O15; P46; F22; I24; 330; migration; traps; poverty; inequality; education; skill